Effect of modified subcostal anterior quadratus lumborum block on perioperative opioid consumption in patients undergoing gynecologic endoscopic surgery - Peng, Chunchao; Fu, Guohui; Chai, Jingping; A, Jide; Guang, Wenhui (Frontiers in Oncology, 2025)
ObjectiveTo assess the impact of ultrasound-guided multimodal anesthesia utilizing a modified subcostal anterior quadratus lumborum block (QLB) in conjunction with general anesthesia on perioperative opioid consumption among patients undergoing gynecologic endoscopic surgery.MethodsA total of 56 patients aged 18–65 years, classified as ASA physical status I-II, with a BMI of 18–30 kg.m², were recruited from Qinghai Provincial People’s Hospital between June 2023 and August 2024 for elective laparoscopic gynecological surgery. According to the random number table method, patients were randomly allocated into two groups: the improved subcostal border anterior quadrate block combined with general anesthesia group (Group A) and the traditional anterior quadrate block combined with general anesthesia group (Group B), each comprising 28 patients. Both groups underwent tracheal intubation and general anesthesia. Before anesthesia induction, patients in Group A received 0.33% ropivacaine (20 ml per side) administered bilaterally under ultrasound guidance for the improved anterior quadratus lumborum block. In contrast, patient in Group B received 0.33% ropivacaine (20 ml per side) administered bilaterally under ultrasound. Following the surgical procedure, both groups were administered controlled patient-controlled intravenous analgesia (PCIA). The administration of perioperative opioids (including intraoperative remifentanil dosage and postoperative opioid dosage) as well as propofol was systematically recorded during the follow-up period; VAS scores were recorded both at dynamic and static at 2 hours, 6 hours,–24 hours, and 48 hours post-intervention; The number of effective analgesic pump activations within–48 hours post-operation was recorded. Additionally, the time of the first anal exhaust and the time of feeding within 48 hours after surgery were documented. Postoperative adverse reactions, including skin itching, nausea or vomiting, and dizziness, were also observed.ResultsCompared to Group B, Group A exhibited a significantly lower dosage of remifentanil (1.49 ± 0.50 mg vs 1.86 ± 0.77 mg, P<0.05) and postoperative opioids (median, 31.79 μg with IQR 23.04-42.75μg vs median, 42.30μgwith IQR 43.26-44.64μg), P<0.05); The dynamic and static VAS scores of patients in Group A were significantly reduced at 2 hours (median 3.00 with IQR 2.00-3.00 vs median 4.00 2with IQR 4.00-4.50, median 3.00 with IQR 2.00-3.00 vs median 3.00 with IQR 3.00-4.00, P<0.001), 6 hours (median 3.00 with IQR 2.00-3.50 vs median 4.00 with IQR 4.00-4.50, median 2.00 with IQR 2.00-3.00 vs median 3.50 with IQR 3.00-4.00, P<0.001) and 24 hours (median 3.00 with IQR 3.00-4.00 vs median 4.00 with IQR 3.50, 4.50, median 3.00 with IQR2.00-3.00 vs median 3.00 with IQR 3.00-4.00, P<0.05); There was no statistically significant difference in dynamic and static VAS scores between the two groups at 48 hours (P=0.568, P = 0.109); The number of analgesic pump compressions in Group A significantly decreased at 48 hours post-surgery (median,0.00 with IQR 1.00-2.00) vs median,1.50 with IQR 0.25-4.00, P<0.05). There was no statistically significant difference in the propofol dosage between the two groups (P=0.667); The A group achieved earlier oral feeding (median 25.00 h with IQR 20.00-30.00 h vs median 33.25 h with IQR 21.50-38.00 h,P<0.05), earlier anal release of gas (median 24.00 h with IQR 21.00-30.00 h vs median 32.00 h with IQR 24.50-38.00, P<0.05); Compared with Group B, the incidence of postoperative dizziness (10% vs 21%, P<0.05), nausea or vomiting (4% vs 17%, P<0.001), and skin pruritus(0% vs 9%, P<0.05) in Group A was significantly reduced (P<0.05).ConclusionCompared to the traditional anterior quadratus lumborum block, the modified subcostal edge anterior quadratus lumborum block significantly decreases perioperative opioid consumption in gynecological laparoscopic surgery patients, effectively alleviates postoperative pain, accelerates gastrointestinal function recovery, and minimizes adverse reactions.